Effects of High Temperature on Rice Grain Development and Quality Formation Based on Proteomics Comparative Analysis Under Field Warming - Liu, Wenzhe; Yin, Tongyang; Zhao, Yufei; Wang, Xueqin; Wang, Kailu; Shen, Yingying; Ding, Yanfeng; Tang, She (Frontiers in Plant Science, 2021)
With the intensification of global warming, rice production is facing new challenges. Field evidence indicates that elevated temperature during rice grain-filling leads to the further deterioration of grain quality. In order to clarify the potential regulatory mechanism of elevated temperature on the formation of rice quality, the DIA mass spectrometry method under the background of field warming was conducted to investigate the regulatory effects of high temperature on grain development and material accumulation pathways. The results showed that a total of 840 differentially expressed proteins were identified during the grain-filling process under elevated temperature. These differentially expressed proteins participated in carbon metabolism, amino acid biosynthesis, signal transduction, protein synthesis, and alternately affected the material accumulation of rice grains. The significant up-regulation of PPROL 14E, PSB28, granule-bound starch synthase I, and the significant down-regulation of 26.7 kDa heat shock protein would lead to the component difference in grain starch and storage proteins, and that could be responsible for the degradation of rice quality under elevated temperature. Results suggested that proteins specifically expressed under elevated temperature could be the key candidates for elucidating the potential regulatory mechanism of warming on rice development and quality formation. In-depth study on the metabolism of storage compounds would be contributed in further proposing high-quality cultivation control measures suitable for climate warming.